PENGARUH PEOPLE DAN PHYSICAL EVIDENCE TERHADAP KEPUASAN PASIEN DI RSUD BIMA - fillan syah (Jurnal Ilmiah Satyagraha, 2022)
This study aims to determine the effect of people and physical evidence partially and simultaneously on consumer satisfaction at Bima Hospital. Data was collected by distributing questionnaires to 50 patients. Data analysis used validity test, reliability test, classical assumption, multiple linear regression, determination, correlation, t test and f test with SPSS 23.0 application. The results of this study indicate that there is no significant effect of the people variable on consumer satisfaction at Bima Hospital, there is a significant influence of physical evidence on consumer satisfaction at Bima Hospital and there is a significant influence of people and physical evidence on consumer satisfaction at Bima Hospital.